2019
DOI: 10.31674/mjn.2019.v11i02.003
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nurses’ Knowledge of the Glasgow Coma Scale in Intensive Care and Emergency Departments at a Tertiary Hospital in Riyadh City, Saudi Arabia

Abstract: Purpose:The present study determines the factors affecting knowledge of the Glasgow Coma Scale (GCS) of emergency room (ER) and intensive care unit (ICU) nurses who work at a tertiary hospital in Riyadh, Saudi Arabia. Methods: A cross-sectional study with self-administered questionnaire was conducted among 149 ICU and ER nurses conveniently selected at a tertiary hospital in Saudi Arabia. A standardized tool was used to assess knowledge of the GCS. The study adhered to the STROBE guideline for cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
2
9
1
Order By: Relevance
“…Regarding nurses' knowledge about GCS and FOUR scale the current study revealed that the nurses were more knowledgeable about GCS compared to FOUR scale before conducting the training sessions, whereas the nurses routinely used GCS in all studied settings to assess the patients' LOC and the majority of nurses were unacquainted about FOUR scale. That is congruence with other researchers (Albougami, 2019 andChilikova &Dimitrov, 2016). On the other hand, this study showed that CCNs were more knowledgeable about FOUR score compared to GCS after training session, which may be rationalized by the simplicity of conducting FOUR scale similarly to other researchers' findings (Johnson & Whitcomb, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Regarding nurses' knowledge about GCS and FOUR scale the current study revealed that the nurses were more knowledgeable about GCS compared to FOUR scale before conducting the training sessions, whereas the nurses routinely used GCS in all studied settings to assess the patients' LOC and the majority of nurses were unacquainted about FOUR scale. That is congruence with other researchers (Albougami, 2019 andChilikova &Dimitrov, 2016). On the other hand, this study showed that CCNs were more knowledgeable about FOUR score compared to GCS after training session, which may be rationalized by the simplicity of conducting FOUR scale similarly to other researchers' findings (Johnson & Whitcomb, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…Giving a clear, communicable picture of a patient's condition by reporting each one separately as well as summarizing delivers a clear, communicable picture of a patient's condition. The total score is used to classify head injuries as mild (13)(14)(15), moderate (9)(10)(11)(12), or severe (3)(4)(5)(6)(7)(8) (5,6). In patient care, consistent measurement and transmission of the GCS at different times and amongst different observers is critical (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The total score is used to classify head injuries as mild (13)(14)(15), moderate (9)(10)(11)(12), or severe (3)(4)(5)(6)(7)(8) (5,6). In patient care, consistent measurement and transmission of the GCS at different times and amongst different observers is critical (7)(8)(9). The accurate application of measuring scales in the assessment of patients' awareness status is not only required for determining the patient's prognosis, but also as a basis for decision-making, in clinical setups.…”
Section: Introductionmentioning
confidence: 99%
“…In this article, we discuss research articles that we believe can be essential to improving critical care services in emergency departments. The emergency department deals with many critical cases daily being surgical or medical based (Acob, 2018;Albougami, 2019 andAnal, 2021). Applying an evidence-based approach to the resuscitation of emergency cases is important in ensuring the risk and benefit ratio of treating patients is preserved (Azali, & Ludin, 2020& Ludin, & Bajuri, 2020.…”
Section: Introductionmentioning
confidence: 99%